The Effect Of Mental Health Literacy Education On Improving Adolescents' Knowledge And Attitudes Toward Mental Health - Fredy Akbar; Aini Ahmad; Syamsidar Syamsidar (Jurnal Kesehatan Manarang, 2026)
Adolescence is a crucial developmental stage, marked by significant physical, emotional, and social changes that often impact mental health. Although adolescent mental health issues are increasing, awareness and understanding of these issues remain limited, particularly in areas with limited access to information and strong stigma, such as Polewali Mandar Regency, Indonesia. This study aimed to assess the effectiveness of mental health literacy education. A quantitative pre-experimental design with a single-group pretest-posttest was employed, involving 50 high school students aged 15–18 selected using purposive sampling. Participants completed a validated questionnaire to measure their knowledge and attitudes before and after participating in the program, which was delivered face-to-face or online. Educational materials were developed based on the Mental Health Literacy Framework and adapted to local cultural contexts. Data were analyzed using a paired sample t-test, which showed an increase in knowledge scores from 66.4 (pretest) to 84.2 (posttest), and attitude scores from 71.6 to 88.0 after the intervention, with statistical significance (p < 0.001). These findings indicate that mental health literacy education can significantly improve adolescents' knowledge and attitudes regarding mental health. Implementing mental health literacy education has an impact on improving adolescents' understanding and attitudes toward mental health issues. Integrating structured mental health education into the school curriculum, utilizing both face-to-face and digital learning methods, is crucial for increasing awareness of mental health and reducing stigma among adolescents